A psychosocial approach to supporting injured dancers. Issue 3 (3rd July 2019) - Drury, Catherine
ABSTRACT: Professional dancers experience injury as a crisis and threat to identity that often leads to numerous psychosocial concerns. This article describes a group model designed to help injured dancers recover. As a program of The Actors Fund, this 10-week Support Group for Injured Dancers reduces unwanted isolation caused by injury and provides dancers with strategies for stress reduction and healing. The purpose of this article is to aid practitioners in mitigating emotional distress among injured dancers by providing the history and rationale behind the group, an overview of the group's structure and methods, and suggestions for further research and growth.